CsMYB15 positively regulates Cs4CL2-mediated lignin biosynthesis during juice sac granulation in navel orange - Song, Fang; Li, Zixuan; Wang, Ce; Jiang, Yingchun; Wang, Zhijing; He, Ligang; Ma, Xiaofang; Zhang, Yu; Song, Xin; Liu, Jihong; Wu, Liming (Frontiers in Plant Science, 2023)
‘Lane Late’, a late-maturing navel orange cultivar, is mainly distributed in the Three Gorges Reservoir area, which matures in the late March of the next year and needs overwintering cultivation. Citrus fruit granulation is a physiological disorder, which is characterized by lignification and dehydration of juice sac cells, seriously affecting the commercial value of citrus fruits. The pre-harvest granulation of late-maturing navel orange is main caused by low temperature in the winter, but its mechanism and regulation pattern remain unclear. In this study, a SG2-type R2R3-MYB transcription factor, CsMYB15, was identified from Citrus sinensis, which was significantly induced by both juice sac granulation and low temperature treatment. Subcellular localization analysis and transcriptional activation assay revealed that CsMYB15 protein was localized to the nucleus, and it exhibited transcriptional activation activity in yeast. Over-expression of CsMYB15 by stable transformation in navel orange calli and transient transformation in kumquat fruits and navel orange juice sacs significantly increased lignin content in the transgenic lines. Further, Yeast one hybrid, EMSA, and LUC assays demonstrated that CsMYB15 directly bound to the Cs4CL2 promoter and activated its expression, thereby causing a high accumulation of lignin in citrus. Taken together, these results elucidated the biological function of CsMYB15 in regulating Cs4CL2-mediated lignin biosynthesis, and provided novel insight into the transcriptional regulation mechanism underlying the juice sac granulation of late-maturing navel orange.